How Can New Players Establish Themselves in Highly Institutionalized Labour Markets? A Belgian Case Study in the Area of Project‐Based Work. (9th November 2017) - Xhauflair, Virginie; Huybrechts, Benjamin; Pichault, François
Abstract: How can new players seeking to serve nonstandard worker categories (such as project‐based workers) establish themselves into labour markets that are highly institutionalized? This paper explores the case of SMart, a Belgian community‐based labour market intermediary that successfully developed solutions to better represent the interests of project‐based workers and secure their discontinuous careers. Using an organizational legitimacy approach, we find that labour market entry and growth involve different types of boundary‐crossing when addressing the needs of workers that do not fit into established categories. However, to justify boundary‐crossing, the new player must complement its pragmatic work on delivering new services and tools with conceptual (cognitive) and structural (moral) legitimation work.